STRATEGI GURU DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA MELALUI METODE TALKING STICK BERBANTUAN QUESTION BOX PADA MATA PELAJARAN IPAS KELAS VI UPT SDN 271 APUNDI KABUPATEN LUWU TIMUR - Nurul Asma; Nurlaelah; Abdul Wahab; Martini; Muh. Aidil Sudarmono R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the teacher's strategy in implementing the Talking Stick method with the Question Box, to determine student responses, and to analyze changes in students' speaking skills at UPT SDN 271 Apundi, East Luwu Regency, in science learning. This study uses a qualitative approach with a case study type. Data collection techniques include observation, interviews, and documentation, and are analyzed through data reduction, data presentation, and conclusion drawing. The implementation of the Talking Stick method with the Question Box goes through systematic learning planning, implementation, and evaluation stages. This method encourages active student involvement and obtains positive responses as indicated by increased enthusiasm and participation. In addition, students' speaking skills have improved, in terms of courage, fluency, and the ability to express opinions. Thus, the Talking Stick method with the Question Box is effective in improving students' speaking skills in science learning.